BACTERIOLOGICAL EVALUATION OF URINARY TRACT INFECTION (UTI) IN PEDIATRIC PATIENTS. - V. L. KULKARNI; V. L. KULKARNI; D. M. KULKARNI; S. L. NILEKAR (International Journal of Pharma and Bio Sciences, 2014)
Urinary tract infection is one of the most common diseases in children. It is associated with high morbidity and long term complications. The current study was undertaken to determine the bacteriological profile and antibiogram of uropathogens causing UTI among the pediatric age group. The study population included 0 to12 years old patients, who were clinically suspected to have a UTI. The urine samples were collected and processed by conventional microbiological methods and antimicrobial susceptibility testing was performed. Among 352 cases, 64 had their urine culture positive. In Infants, there was a male preponderance for culture proven UTI and in the age group 1-12 years there was female preponderance. Also, overall there was female preponderance. Predominant uropathogens isolated in our study were E.coli followed by Klebsiella species. Most of the isolates were resistant to commonly prescribed antibiotics. Accurate knowledge on local epidemiology and antibiogram of uropathogens among pediatric patients is necessary for treatment.